THE EFFECT OF VARIATION OF VOLUME SOLUTION OF WULUH STRAWELL AND KEY ORANGE SITE ON PH VALUE, ELECTRICAL PROPERTIES AND CHANGES IN ELECTRODE MASS - Zafira Amalia Nasution; ratni sirait; abdul halim daulay (Universitas Islam Negeri Sumatera Utara Medan, 2021)
Research has been carried out on